The Acceptance of Ar-Rahnu Scheme Among Rural Population - Mohamed, Suhana; Sham, Rohana; Jaffar, Haliza Hirza; Latif, Ruziah A; Zaharum, Zaibedah; Zainal Abidin, Rabiatul Alawiyah; Mohd Hasan Abdullah, Norhasniza; Ahmad, Zuraidah; Md Don, Mohd Ali; Hassan, Sallaudin; Wan Mohamad, Wan Munirah; Raja Mohd Rasi, Raja Zuraidah; et al. (Springer, 2016)
The objective of this study was to identify the factors that influence the acceptance of Ar-Rahnu Scheme among the rural population. Ar-Rahnu Scheme is a widely known Islamic pawn broking system in Malaysia. This scheme is currently offered by several institutions in Malaysia, and its acceptance by customers is a c-